Ibsen's Unexpected Triumph. - Holtcamp, Victor (Alabama Review, 2012)
An essay is presented that reconstructs the performance of the play "Peer Gynt" written by Norwegian playwright Henrik Ibsen as performed in Seattle, Washington, in the 1930s and beyond. The author utilizes the Seattle, Washington, Repertory Playhouse Papers located in the Manuscript Division of the University of Washington Archives.